Alcohol consumption among Filipino college students - Monte, Rowena N.; Dela Cruz, Jovita S.; Buan, Aivi R. (2016)
Reducing alcohol use among Filipino college students is one of the priorities of Philippine colleges and state universities in terms of looking after the holistic growth of many students in their respective schools. Perhaps one of the causes why the said concern on alcohol consumption is rampant among Filipino college students is that educators and parents focus mostly on intervention rather than prevention. Time spent learning the effects of alcohol consumption is greater than preventing the problem. In this study, a descriptive methodology was employed specifically using systematic review in identifying possible preventive strategies in reducing problematic alcohol consumption among Filipino college students. Included in this discussion is the awareness of the factors associated with alcohol consumption in order to come up with correct and effective alcohol prevention strategies. Factors that appeared in this review will be briefly discussed. Developing effective prevention strategies helps in ascertaining preventive strategies of consuming alcohol.
Keywords: College students -- Alcohol use; Drinking of alcoholic beverages; Prevention of alcoholism